Cell Wall Lytic Enzymes And Their Role In Bacteriophages Infection - I Putu Sudiarta; Gusti Ngurah Alit Susanta Wirya (Agriculture Faculty of Flores University, 2011)
Use of chemical pesticides has been shown to have many negative side effects, such as insecticide resistance and resurgence, an outbreak of secondary pests and diseases, the disappearance of parasitoid and predator species as well as residual effects on food crops and on the environment. Over the past 60 years, both the number of agricultural toxins in the environment and incidence rates of toxin-related diseases has increased dramatically. The most effective way to combat this problem is through the use of natural predators. One of the best examples of this is the use of host-specific bacteriophages to control bacterial diseases. The mechanism of infection is a very interesting one. To break through the bacterial cell wall the bacteriophages must produce a range of lytic enzymes. This review will examine and discuss studies of these site-specific cell wall lytic enzymes and their roles in the infection of bacteriophages.